2019
DOI: 10.3892/etm.2019.7875
|View full text |Cite
|
Sign up to set email alerts
|

Matrine prevents the early development of hepatocellular carcinoma like lesions in rat liver

Abstract: Matrine (C15H24N2O) is an alkaloid extracted from the Chinese herb Sophora flavescens that has anti-fibrotic and anti-cancer properties. The aim of the present study was to determine the chemopreventive effect of matrine on the development of primary hepatocellular carcinoma (HCC) and its possible association with the suppression of the Notch signaling pathway. The rats were randomly divided into four groups: Control, model, low-dose matrine and high-dose matrine groups. The model was established by combining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 41 publications
(47 reference statements)
0
10
0
Order By: Relevance
“…Matrine acts on tissues and cells through multiple signaling pathways, exerting pharmacological functions such as anti-tumor, anti-inflammatory, and anti-fibrosis. Studies have reported that matrine has a strong inhibitory effect on various tumor cells, and its molecular mechanism lies in regulating cell cycle progression, promoting apoptosis, inhibiting tumor invasion and metastasis, inducing autophagy, reversing multidrug resistance in tumor cells, and regulating metabolism through mediating multiple cellular signaling pathways such as the PI3K/AKT/mTOR, 13–43 NF-κB, 77–85 Wnt/β-catenin, 101–108 MAPKs, 111–118 Notch, 131 , 132 and JAK-STAT 136–138 pathways. Non-coding RNAs also play an important role in these events, 16 , 19 , 22 , 41 , 42 , 102 , 103 , 105 indicating that the anti-tumor mechanisms of matrine involve multi-pathways, multi-targets, and multi-systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Matrine acts on tissues and cells through multiple signaling pathways, exerting pharmacological functions such as anti-tumor, anti-inflammatory, and anti-fibrosis. Studies have reported that matrine has a strong inhibitory effect on various tumor cells, and its molecular mechanism lies in regulating cell cycle progression, promoting apoptosis, inhibiting tumor invasion and metastasis, inducing autophagy, reversing multidrug resistance in tumor cells, and regulating metabolism through mediating multiple cellular signaling pathways such as the PI3K/AKT/mTOR, 13–43 NF-κB, 77–85 Wnt/β-catenin, 101–108 MAPKs, 111–118 Notch, 131 , 132 and JAK-STAT 136–138 pathways. Non-coding RNAs also play an important role in these events, 16 , 19 , 22 , 41 , 42 , 102 , 103 , 105 indicating that the anti-tumor mechanisms of matrine involve multi-pathways, multi-targets, and multi-systems.…”
Section: Discussionmentioning
confidence: 99%
“…Shi et al 132 established a rat model of drug-resistant hepatocyte and further explored the effect of matrine on the early changes of liver carcinogenesis. They indicated that matrine treatment significantly inhibited the development of precancerous lesions, including restoration of hepatic cord structure, reduction of hepatic edema and degeneration, and changes in AFP and ALB expression.…”
Section: Matrine Exerts Pharmacological Effects Through the Notch Sig...mentioning
confidence: 99%
“…Although autophagy induction or inhibition has been reported to be implicated in the antitumour activity of matrine against several solid tumours [13,17], the role of autophagy and the underlying mechanism remain unobvious in esophageal carcinoma. MDR is a refractory outcome of chemotherapy and is defned as the resistance of cancer cells to multiple chemotherapeutic drugs with different structures and mechanisms of action [18].…”
Section: Discussionmentioning
confidence: 99%
“…A combinational treatment of S. moorcroftiana alkaloids with albendazole displayed better therapeutic effects than albendazole alone against liver echinococcosis, and alleviated liver injury (Zhang et al 2018a ). A recent study also suggested that aloperine ( 284 ) could prevent the early development of hepatocellular carcinoma like lesions in rat liver (Shi et al 2019 ).…”
Section: Biological Effectsmentioning
confidence: 98%